Ratings of perceived fatigue predict fatigue induced declines in muscle strength during tasks with different distributions of effort and recovery. (August 2019) - Whittaker, Rachel L.; Sonne, Michael W.; Potvin, Jim R.
Abstract: The purpose of this study was to quantify the relationship between ratings of perceived fatigue (RPF), using a modified Borg CR-10 scale, and muscle fatigue accumulation, as defined by maximal voluntary contraction strength (MVC) declines, during two complex MVC-relative tasks (conditions) that cause muscle fatigue and allow recovery. Nine female participants completed the fatiguing tasks, composed of a series of submaximal, isometric efforts (task plateaus) requiring isometric flexion at the distal interphalangeal joint of the thumb. Significant partial correlations between RPF and MVC, while controlling for task plateau intensity (%MVC), were found in 6/9 participants. A significant linear regression model, explaining 86.2% of the variance in mean MVC decline, was obtained with 3 predictor variables: mean RPF (p < 0.001), Task Plateau (p < 0.001), and the interaction between mean RPF and Task Plateau (RPF × Task Plateau; p = 0.014). The observed linear relationship between RPF and MVC declines, both at the participant and group level support, the use of RPF to estimate the instantaneous fatigue status of the muscle in tasks that allow both muscle fatigue and recovery.